ANALYSIS OF CORRUPTION ERADICATION COUNTERMEASURES AGAINST FLEEING CORRUPTORS UNDER INTERNATIONAL LAW (CASE STUDY OF EXTRADITION TREATY BETWEEN INDONESIA AND SINGAPORE) - Ramadhan, Athallah Ariq; Alim, Fikri Nur; Jaelani, Achmad; Fasyehhudin, Mohamad; Irawan, Benny; Zakiran, Asep Hakim (Faculty of Law Sriwijaya University, 2024)
Extradition treaties are agreements between countries worldwide that involve the extradition of suspects or perpetrators of crimes, including economic crimes. Extradition treaties are between two countries to prevent transnational or cross-border crimes where the perpetrators flee to another country because they do not want to take responsibility for what they did. Extradition treaties have binding legal force following international law because they are international treaties. The extradition treaty made by Indonesia and Singapore is evidence of their positive cooperation in protecting law enforcement. Over the past few years, suspected Indonesian economic criminals have fled to Singapore with large amounts of money and capital. While Indonesian law cannot be applied to Singaporean territory, in the event of an extradition treaty between Indonesia and Singapore, it would have significant consequences. Suspected economic criminals can be brought back to Indonesia to be sentenced per applicable laws, while Singapore cannot. So this research aims to analyze the Extradition Treaty between Indonesia and Singapore According to International Law (Case Study of Tackling Corruption).